Limits of intravascular contrast extravasation on computed tomography scan to define the need for pelvic angioembolization in pelvic blunt trauma: a specific assessment on the risk of false positives. Issue 3 (September 2018) - Ramin, Séverin; Hermida, Margaux; Millet, Ingrid; Murez, Thibault; Monnin, Valerie; Hamoui, Mazen; Capdevila, Xavier; Charbit, Jonathan
Abstract : BACKGROUND: The objective was to assess the predictive performance of different intravascular contrast extravasation (ICE) characteristics for need for pelvic transarterial embolization (TAE) to determine the risk factors of false positives. METHODS: A retrospective study was performed in our trauma center between 2010 and 2015. All severe trauma patients with pelvic fracture were included. Pelvic ICE characteristics on computed tomography (CT) scan were studied: arterial (aS 2 ICE ), portal surface (pS 2 ICE ), and extension (exS 2 ICE ) anatomic relationships. The overall predictive performance of ICE surfaces for pelvic TAE was analyzed using receiver operating characteristic curves. The analysis focused on risk factors for false positives. RESULTS: Among 311 severe trauma patients with pelvic ring fracture (mean age, 42 ± 19 years; mean Injury Severity Score, 27 ± 19), 94 (30%) had at least one pelvic ICE on the initial CT scan. Patients requiring pelvic TAE had significantly larger aS 2 ICE and pS 2 ICE than others ( p = 0.001 and p = 0.035, respectively). The overall ability of ICE surfaces to predict pelvic TAE was modest (aS 2 ICE area under the receiver operating characteristic curve, 0.76 [95% confidence interval, 0.64–0.90]; p = 0.011) or nonsignificant (pS 2 ICE and exS 2 ICE ). The high-sensitivity threshold was defined as aS 2 ICE 20 mm 2 or more. Using this threshold, 76% of patients were false positives. Risk factors for false positives were admission systolic blood pressure of 90 mm Hg or greater (63% vs 20%; p = 0.03) and low transfusion needs (63% vs 10%; p = 0.009), extravasation in contact with complex bone fracture (78% vs 30%; p = 0.008), or the absence of a direct relationship between extravasation and a large retroperitoneal hematoma (100% vs 38%; p < 0.001). CONCLUSION: A significant pelvic ICE during the arterial phase does not guarantee the need for pelvic TAE. Three quarters of patients with aS 2 ICE of 20 mm 2 or more did not need pelvic TAE. Several complementary CT scan criteria will help to identify this risk of false positives to determine adequate hemostatic pelvic procedures. LEVEL OF EVIDENCE: Therapeutic study, level IV. Abstract : Supplemental digital content is available in the text.